On the effect of intramolecular H-bonding in the configurational assessment of polyhydroxylated compounds with computational methods : The hyacinthacines case - Zanardi, María Marta (2019)
Fil: Zanardi, María Marta. Pontificia Universidad Católica Argentina. Facultad de Química e Ingeniería del Rosario; Argentina